ASESMEN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI TK IMMANUEL KIDS - Artha Mahindra Diputera; Anita Yus; Debby Selviana Waruwu; Elsa Pretty Simanjuntak; Emy Florentina Barus; Oktarini Fajriah; Palija Lubis; Tio Aquandri Siringo Ringo (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Social emotional development of early childhood needs to get the focus of parents and teachers so that children can be accepted by their social environment. This study aims to determine the assessment of social emotional abilities of children aged 5-6 years at Immanuel Kids Kindergarten Medan Amplas. This research method uses descriptive research with a qualitative approach. In this study the assessment used was statistical data analysis techniques. The instrument used in this study used an observation sheet. With a rating scale in the form of BB (Not Developing), MB (Starting to Develop), BSH (Developing According to Expectations). The findings show that as many as 5 children with MB criteria (Beginning to Develop), 2 children with BSH criteria (Developing According to Expectations) and 8 children receiving BB criteria (Not Yet Developed). So it can be concluded from the social emotional assessment carried out in Immanuel Kids Kindergarten that needs to be developed. Because there were 8 children with BB criteria (Not yet Developed) out of 15 children who were observed. And got a score of 53.3%.